Public perception of COVID-19's global health crisis on Twitter until 14 weeks after the outbreak. - Abdo, Muhammad S; Alghonaim, Ali S; Essam, Bacem A (Digital Scholarship in the Humanities, 2021)
Because language represents advanced aspects of human cognition, studying linguistic styles and figurative meaning have proven effective in measuring embodied cognition about the external world. This article defines the most worrisome topics people discussed from Weeks 1 to 14 after the outbreak and compares the message delivered by the literal use of words to the figurative use of metaphoric expressions. We bootstrapped representative data from Twitter over 14 weeks since the inception of the outbreak to be analyzed thematically using the Linguistic Inquiry and Word Count (LIWC) 2015 software as well as corpus tools. The MetaNet database, corpus tools, and manual annotation were used to detect expressions that can be linguistically mapped to the formalized list of conceptual metaphors. The most frequently tagged themes included 'the outbreak of the pandemic, its epidemiology, its prophylaxis measures, national and world economies, media', as well as the 'signs and symptoms of COVID-19'. Although LIWC-based analysis showed English-speaking tweeters maintained high levels of analytical thinking, elevated levels of anger, anxiety, and doubtfulness, there were discrepancies and improper conceptualization of the clinical picture of the pandemic.